Cancer cell-autonomous TRAIL-R signaling promotes KRAS-driven cancer progression, invasion, and metastasis - von Karstedt, Silvia; Conti, Annalisa; Nobis, Max; Montinaro, Antonella; Hartwig, Torsten; Lemke, Johannes; Legler, Karen; Annewanter, Franka; Campbell, Andrew D; Taraborrelli, Lucia; Grosse-Wilde, Anne; Coy, Johannes F; et al. (Cancer cell, 2015)
Many cancers harbor oncogenic mutations of KRAS. Effectors mediating cancer progression, invasion, and metastasis in KRAS-mutated cancers are only incompletely understood. Here we identify cancer cell-expressed murine TRAIL-R, whose main function ascribed so far has been the induction of apoptosis as a crucial mediator of KRAS-driven cancer progression, invasion, and metastasis and in vivo Rac-1 activation. Cancer cell-restricted genetic ablation of murine TRAIL-R in autochthonous KRAS-driven models of non-small-cell lung cancer (NSCLC) and pancreatic ductal adenocarcinoma (PDAC) reduces tumor growth, blunts metastasis, and prolongs survival by inhibiting cancer cell-autonomous migration, proliferation, and invasion. Consistent with this, high TRAIL-R2 expression correlates with invasion of human PDAC into lymph vessels and with shortened metastasis-free survival of KRAS-mutated colorectal cancer patients.